Mechanical exfoliation and layer number identification of single crystal monoclinic CrCl3. (6th July 2020) - Kazim, S; Alì, M; Palleschi, S; D'Olimpio, G; Mastrippolito, D; Politano, A; Gunnella, R; Di Cicco, A; Renzelli, M; Moccia, G; Cacioppo, O A; Alfonsetti, R; et al.
Abstract: After the recent finding that CrI3, displays ferromagnetic order down to its monolayer, extensive studies have followed to pursue new two-dimensional (2D) magnetic materials. In this article, we report on the growth of single crystal CrCl3 in the layered monoclinic phase. The system after mechanical exfoliation exhibits stability in ambient air (the degradation occurs on a time scale at least four orders of magnitude longer than is observed for CrI3 ). By means of mechanical cleavage and atomic force microscopy (AFM) combined with optical identification, we demonstrate the systematic isolation of single and few layer flakes onto 270 nm and 285 nm SiO2 /Si (100) substrates with lateral size larger than graphene flakes isolated with the same method. The layer number identification has been carried with statistically significant data, quantifying the optical contrast as a function of the number of layers for up to six layers. Layer dependent optical contrast data have been fitted within the Fresnel equation formalism determining the real and imaginary part of the wavelength dependent refractive index of the material. A layer dependent (532 nm) micro-Raman study has been carried out down to two layers with no detectable spectral shifts as a function of the layer number and with respect to the bulk.